EFFECT OF FORWARD HEAD POSTURE ON SENSORIMOTOR INTEGRATION (International Journal of Physiotherapy, 2017)
Background: Forward head posture (FHP) is a common type of postural distortion seen clinically, whereby an anterior shift of the head position occurs. Ideal posture is considered to be present when the external auditory meatus is aligned with the vertical line. There were different assessment methods of FHP and the measurement of craniovertebral (CV) angle considered as the most common assessment methods of FHP, The smaller the angle, the greater the FHP. Muscle strain considered as one of the complications of FHP, repetitive strain of the muscle lead to a change in the way of the brain processes the incoming sensory information and subsequent motor output to muscles, a process known as sensorimotor integration(SMI). This study was conducted to measure the neurophysiological effect of FHP on SMI.Methods: Sixty volunteers participated in the study,30 normal subjects with CV angle≥49 are in group A (Normal), 30 forward head subjects with CV angle ≤49 are in group B (forward head). The amplitude of Cortical Somatosensory evoked potential (SSEPs) of N30-P22, N20-P25 and N24-P22 N30 complex (N30-P22), N20 complex (N20-P25) and N24 complex(N24-P22) of SEPS were recorded for both groups after stimulation of the right median nerve.Results: There was a significant increase in the cortical amplitude of N30-P22, N20-P25 and N24-P22 of SEPS in the group (A) compared with a group (B) as p-value was ≤ 0.05.Conclusion: forward head posture affects SMI through changing the response of CNS to afferent input, as demonstrated by attenuation of cortical STEPS in the group (B) compared with a group (A).